PENGARUH LABEL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN RTD TEA LESS SUGAR(STUDI PADA MEMBER PUSAT KEBUGARAN DI WILAYAH SURABAYA SELATAN) - AMIRUDDIN AL-FARISI, MOHAMMAD (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this study is to analyze and discuss the influence of the label and product quality partially on purchasing decisions RTD tea less sugar. The sampling technique used was nonprobability sampling. The sample taken are 210 people. Respondents in this study is a member of the fitness center in the south of Surabaya. The scale of measurement in this study using a Likert scale. Measuring instrument used was a questionnaire. Analysis of data using multiple linear regression model. The results showed that the label has positive influence on purchasing decisions, and product quality has positive influence on purchase decisions. Keyword : label, product quality, and purchase decisions.